Reproductive Characteristics of Doublespotted Queenfish, Scomberoides Lysan (Actinopterygii: Perciformes: Carangidae), from Sri Lankan Waters: Implications for Fisheries Management - Thulasitha; William, S.; Sivashanthini, K. (Acta Ichthyologica et Piscatoria, 2013)
The doublespotted queenfish, Scomberoides lysan (Forsskål, 1775), is one of the most important and highly priced food fishes popular for dry fish production in Sri Lanka. Knowledge of spawning pattern and season are important for the management of S. lysan. The biology of S. lysan is poorly known, however, and no specific management regime is available for this species in Sri Lanka. The presently reported study is the first attempt to understand the reproductive characteristics of S. lysan with implications for its management.
Keywords: FECUNDITY; GONADOSOMATIC INDEX; SCOMBEROIDES LYSAN; SIZE AT MATURITY; SPAWNING SEASON